2008
DOI: 10.1111/j.1582-4934.2008.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

ZHX2 is a repressor of α‐fetoprotein expression in human hepatoma cell lines

Abstract: The zinc-fingers and homeoboxes 2 (ZHX2) protein was shown previously to be involved in postnatal repression of α-fetoprotein (AFP) in mice. More recently, loss of ZHX2 expression was often found in human hepatcellular carcinoma (HCC), where AFP is frequently reactivated. Using HepG2 and HepG2.2.15, which express high AFP levels, we show that ZHX2 overexpression significantly decreases of AFP secretion in a dose dependent manner. Furthermore, using LO2 and SMMC7721 cells, which express low AFP levels, we use s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 32 publications
4
54
1
Order By: Relevance
“…For example cancer cells may carry out increased de novo fatty acid synthesis irrespective of extracellular lipid levels [Kuhajda, 2000;Menendez and Lupu, 2007]. In addition cancer cells including HepG2 cells express high levels of a-fetoprotein which is involved in lipid metabolism [Kumbla et al, 1991;Mizejewski, 2004;Shen et al, 2008]. Thus in the present study we first prepared steatotic cells using the L-02 cell line, which is derived from normal human hepatocytes.…”
Section: Discussionmentioning
confidence: 98%
“…For example cancer cells may carry out increased de novo fatty acid synthesis irrespective of extracellular lipid levels [Kuhajda, 2000;Menendez and Lupu, 2007]. In addition cancer cells including HepG2 cells express high levels of a-fetoprotein which is involved in lipid metabolism [Kumbla et al, 1991;Mizejewski, 2004;Shen et al, 2008]. Thus in the present study we first prepared steatotic cells using the L-02 cell line, which is derived from normal human hepatocytes.…”
Section: Discussionmentioning
confidence: 98%
“…They also found that AFP expression in BALB/cJ mouse liver was caused by the ZHX2 mutation. Shen et al 22 found ZHX2 interacted with hepatocyte NF-1 binding sites to repress AFP transcription in HCC cell lines. Furthermore, a clinical study demonstrated that ZHX2 expression is negatively related with AFP expression in HCC samples.…”
Section: Zhxs Signalingmentioning
confidence: 99%
“…ZHX2 8 comprise 873 amino acid residues and shares two C2H2-typed zinc finger domains and five homeodomains with other members of the family, i.e., ZHX1 and ZHX3. In previous studies 9,10 , ZHX2 expressed ubiquitously in various tissues, and was identified as a transcriptional repressor for foetal-expressed genes, e.g., α-foetoprotein and glypican. The homeobox genes generally encode transcription factors that can either activate or repress target genes in a temporal and spatial manner 11 .…”
Section: Introductionmentioning
confidence: 94%
“…Loss of ZHX2 function in the liver causes persistent α-foetoprotein production in adult mice. Suppression of α-foetoprotein production in hepatocellular cancer cell line by ZHX2 is dependent on the HNF1 binding site 9 . Taken together, by an unknown mechanism, ZHX2 with or without other transcription factor(s) might be involved in the switching off of the γ-globin gene during adulthood.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation